TINGKAT DAN POLA DISTRIBUSI INFESTASI PENGGEREK BATANG JAGUNG OSTRINIA FURNACALIS (LEPIDOPTERA: CRAMBIDAE) DI PADANGSIDIMPUAN - Muhammad Agung Permadi; Qorry Hilmiyah Harahap (Universitas Medan Area, 2019)
Ostrinia furnacalis Guenee as known as Asian corn stem borer is one of the main pests in corn cultivation practices in Indonesia. Besides Indonesia, these pests attack in other Asian regions such as Central Asia, East Asia, and also Australia. This study was aimed to measure the intensity of infestation and to analyze patterns of distribution of O. furnacalis in corn field. The observations of intensity and infestation distribusiton were held on 12 corn plantations owned by farmers in six sub-districts of Padangsidimpuan. Results showed that The lowest infested area of O. furnacalis larvae was 1.1%, while the highest was 4.31%. O. furnacalis larvae infestations at each plant in each plantations has a random distribution and the distribution was varies among corb fields.